(untitled) (Journal of Applied Oral Science, 2016)
Increased matrix metalloproteinases (MMPs) activity is a hallmark of periapical granulomas. However, the factors underlying the MMPs expression modulation in healthy and diseased periapical tissues remains to be determined. Objective In this study, we evaluated the association between the MMP1-1607 polymorphism (rs1799750) and pro-inflammatory milieu elements with MMP-1 mRNA levels in vivo. Material and Methods MMP1-1607 SNP and the mRNA levels of MMP-1, TNF-a, IFN-g, IL-17A, IL-21, IL-10, IL-4, IL-9, and FOXp3 were determined via RealTimePCR in DNA/RNA samples from patients presenting periapical granulomas (N=111, for both genotyping and expression analysis) and control subjects (N=214 for genotyping and N=26 for expression analysis). The Shapiro-Wilk, Fisher, Pearson, Chi-square ordinal least squares regression tests were used for data analysis (p